Badan Usaha Milik Desa Gumbregah Dalam Mengelola Wisata Bukit Cinta Watu Prahu Desa Gununggajah - Pangesti, Aprilia Dwi; Mu’arifuddin, Mu’arifuddin (Universitas Pahlawan Tuanku Tambusai, 2024)
Indonesia's tourism industry is growing rapidly, although it still faces challenges in infrastructure, quality of Human Resources (HR), and environmental preservation. In Gununggajah Village, the Gumbregah Village-Owned Enterprise (BUMDes) manages Bukit Cinta Watu Prahu to improve the local economy through community participation, despite limited resources and skills. This study aims to describe the role of BUMDes, the obstacles faced, and community participation in managing Bukit Cinta Watu Prahu tourism. This study uses a qualitative descriptive approach in data collection with research subjects including the BUMDes chairman, BUMDes secretary, BUMDes treasurer, village head and 2 community members. This study uses a qualitative approach in data collection with observation, interview and documentation methods. Data validity techniques use source methods, techniques and theories. The results of the study show that BUMDes has played a good role in managing Bukit Cinta Watu Prahu tourism. The role of BUMDes as a facilitator, mediator, motivator and dynamic has succeeded in creating synergy between the government, community, and local economic sectors. Despite challenges such as limited infrastructure and human resources, BUMDes is able to encourage active community participation in tourism management, improve service quality, and maintain environmental sustainability. In addition, tourism management based on mutual cooperation and the use of results for improving facilities and empowering the local economy has had a positive impact on the Gununggajah Village community.